Tra saeculum e mysterium fidei. La chiesa cattolica in regime di lockdown - Bova, Vincenzo (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The consequences of the pandemic on the presence of the Catholic Church. The relation State-Church. The adaptive strategies by the church followers and by the religious institution. The role played by Pope Francis.The Catholicism between visibility and evanescence. The questions asked to the institution and the possible outcomes for the future way of believing.